Magnetic Reversal of Cylindrical Nickel Nanowires with Modulated Diameters - Escrig-Murua, J (2011)
Anodic alumina membranes with modulated pore diameters serve as template for the preparation of magnetic nanowires. Filling the pores with Ni by electrodeposition delivers wires replicating the variation in modulation in pore diameter from 80 to 160 nm. Such structures are of interest for the observation and control of magnetic domain wall motion. Single-object characterization utilizing the magneto-optical Kerr effect magnetometry evidences a strong correlation between geometric parameters and magnetic properties. Ensemble magnetization measurements with a superconducting quantum interference device show the effect of dipolar interactions. Analytical models can reproduce the lowering of coercivity due to the presence of enhanced stray fields within the array. Magnetic force microscopy at individual wires indicates the presence of a strong stray field in the vicinity of the diameter change. The preparation technique demonstrates a mass production method of nano-objects with designed geometric irregularities, which could be used to control the motions of magnetic domain walls. © 2011 American Institute of Physics.